The Importance of Marriage in Jane Austen’s Novels (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The following article reveals the significance of marriage in Jane Austen’s novels. The writer's style is analyzed through the image of the heroes of the work, and the important role of marriage in society is revealed with the examples from the novel. The work focuses on the analysis of social life and gender issues, the role and relationship of women and men in society, family and marriage relations, as well as the different and similar views of men and women in relation to them.